A hierarchical coloured Petri net model of fleet maintenance with cannibalisation - Sheng, Jingyu; Prescott, Darren (Elsevier, 2017)
Cannibalisation refers to a maintenance action where an unserviceable part in an inoperative platform is replaced by a serviceable part of the same type from another platform. It helps a fleet meet operational requirements when spares are in short supply but leads to more maintenance tasks to be carried out. In practice, cannibalisation may be performed in an unrestricted manner, or through the use of cannibalisation birds. A cannibalisation bird is a platform which is selected as the primary source of cannibalisation, while any inoperative platform can be a cannibalisation source under the unrestricted policy. In order to aid fleet managers in making cannibalisation-related decisions, this paper presents a hierarchical coloured Petri net (HCPN) model of a fleet operation and maintenance process which considers mission-oriented operation, multiple level maintenance, multiple cannibalisation policies (no cannibalisation, unrestricted cannibalisation and cannibalisation bird), maintenance scheduling and spare inventory management. The model is applied to an example fleet to compare the effects of different cannibalisation policies on fleet performance using a number of performance measures related to reliability and maintenance and to optimise the number of cannibalisation birds used and the length of time that a platform is taken as a cannibalisation bird for the fleet.